## What is a semiconductor?

### What is a semiconductor?

Those material, which have resistivity or conductivity intermediate to metals or insulator, called semiconductor. The band gap of semiconductor is less than 3 eV. The band gap of Ge and Si respectively 1.1 eV and 0.7 eV.
Si, Ge, GaAs, CdTe etc are examples of semiconductors.
The band gap of Ge and Si respectively 1.1 eV and 0.7 eV.

Si, Ge and C are elemental semiconductor. Examples of compound semiconductors are following:
Inorganic: Cds, GaAs, Cdse, InP etc.
Organic: Anthracene, doped pthalocyanines etc.
Organic Polymers: Polypyrolle, Polyaniline, Polythiophene etc.

An intrinsic semiconductor is one which is made of the semiconductor material in its totally pure form and with no impurities or lattice defects.

If we added small amount ( parts per million, ppm ) of suitable impurities in pure semiconductor , Then this process is called dopping and suitable impurity is called dopent. Dopped intrinsic or pure semiconductor is called extrinsic semiconductor.

There are two types of extrinsic semiconductors-

(a) n-type semiconductor

The pentavalent impurities eg. Phosphorus, Arsenic, Antimony, Bismith etc are referred to as donor impurities. If pure semiconductor is dopped with donor impurities then this type of semiconductor is called n-type semiconductor.

(b) p-type semiconductor

Trivalent impurities eg. Boron, Aluminium, Indium and galium are referred as accepter impurities. If pure semiconductor is dopped with acceptor impurities then this type of semiconductor is called p-type semiconductor.

## Logrithm formula

### Formulae of Logarithm

• loga mn = loga m + loga n
• loga m/n = loga m – loga n
• loga mn = n loga m
• loga m= logb m × loga b
• loge m = 2.3026 log10 m
• log10 m = 0.4343 loge m

### Logrithmic Series

• loge ( 1+x ) = x – x2/2 + x3/3 – x4/4 +……
• loge ( 1-x ) = -[x + x2/2 + x3/3 + x4/4 +……]
• loge ( 1+x ) / ( 1-x ) = 2 [x + x3/3 + x5/5 +……]

## Factors

• ( a+b )2 = a2 + b2 + 2ab
• ( a-b )2 = a2 + b2 – 2ab
• ( a2 – b2) = ( a+b ) ( a-b )
• ( a2 + b2 ) = ( a+b )2– 2ab
• ( a+b )3 = a3 + b3 + 3ab( a+b )
• ( a-b )3 = a3 – b3 – 3ab( a-b )
• ( a+b+c)2 = a2 + b2 + c2 +2(ab + bc + ac )
• a3 + b3 + c3 – 3 abc = ( a+b+c ) ( a2 + b2 + c2 – ab – bc – ac )
• ( a+b )4 = a4 + b4 + 2ab ( 2a2 + 3ab + 2b2)
• ( a-b )4 = a4 + b4 – 2ab ( 2a2 + 3ab – 2b2 )